Economics of education – definition of the position - Wolter, Stefan C. (Swiss Journal of Educational Research, 2002)
Judging by the many studies done in the field concerning the economics of education over the last ten years, this discipline, which represents the interface between economics and education, is enjoying a Renaissance. This article attempts to summarize and interpret some of the themes and findings of the most recent research done in the field. The themes selected have been organized into two sections: one, research questions that have more of a human capital orientation, and two, more traditional economics of education questions that focus on the financing of education and its production in the educational system. The article concludes that despite the impressive amount of research currently being conducted, most questions remain unanswered or subject to dispute. More investment, and in particular a better mooring of the economics of education in the scientific community are thus needed if the economics of education is to fulfill the growing expectations of those involved in shaping educational policies and administering educational systems.